Does import trade liberalization worsen residents' health? Evidence from China - Ming Chen; Hongbo Wang (Frontiers Media S.A., 2024)
Health is important to human capital and national sustainable development. Based on the latest Chinese Family Panel Studies (CFPS), this paper uses the IVprobit model to test the impact of import trade liberalization on residents' health from the micro-individual perspective and further explores its mechanism. The results indicate that import trade liberalization brings hidden health costs, and that the negative effects on the health of people in eastern China or rural areas, people with a low education background, people under 60 years of age, and women are more significant. In areas with more serious environmental pollution, the health deterioration effect of expanding imports is more obvious. Increasing green coverage and optimizing the quality of public services can effectively alleviate this negative impact. Import trade liberalization does not affect residents' health through income gap, therefore when carrying out import trade liberalization the government should pay greater attention to the health status of the specified groups, adopt various means to improve the ecological and living environments, reduce pollution emissions, optimize the supply of public services, and ultimately improve residents' overall health level.